Malaysia’s Changing Federal-State Relations – The Sarawak Imbroglio : Constitutional Amendment Setback - Sukhani, Piya (2019)
Pakatan Harapan failed to secure two-thirds majority in Parliament for its constitutional amendment to restore Sabah and Sarawak’s equal status in Malaysia. Why did Sarawak abstain from voting for this amendment? What might be the ramifications for the federal government?